Hydrometallurgical Process for Recovery of Cadmium from the Plant Sewage Sludge - Mohammadi Moreveg, Parvin; Golchoubian, Hamid (Asian Journal of Chemistry, 2010)
A hydrometallurgical process has been developed for recovery of cadmium from the zinc plant sewage sludge. The residue obtained from drying of the sludge contains great quantity of zinc and cadmium and also along with lead, iron, nickel, copper and cobalt. The process consists of the following five major unit operations: (1) leaching: 2 mol L-1 ratio of 4: 1, 25ºC and 1.5 h; (2) precipitation of iron, copper and lead: pH 5.4, 2 h, ambient temperature; (3) precipitation of nickel and cobalt: at pH 5.4, 80-85ºC, 20 min by an addition of dimethylglyoxime; (4) cementation of cadmium metal: at pH 4.7-5.0, 40-50ºC, 30 min by an addition of zinc metal; (5) purification of cadmium by heating the impure cadmium with sodium hydroxide in a blowing oven at temperature of 500-600ºC and then washing it with sulfuric acid, L/S hot water. The total recovery of cadmium was found to be approximately 89%.